A quantitative easing experiment - Adrian Penalver; Nobuyuki Hanaki; Eizo Akiyama; Yukihiko Funaki (Osaka University, Institute of Social and Economic Research (ISER), 2020)
We experimentally investigate the effect of a central bank buying bonds for cash in a quantitative easing (QE) operation. In our experiment, the bonds are perfect substitutes for cash and have a constant fundamental value which is not affected by QE in the rational expectations equilibrium. We find that QE raises bond prices above those in the benchmark treatment without QE. Subjects in the benchmark treatment learned to trade the bonds at their fundamental value but those in treatments with QE became more convinced after repeated exposure to the same treatment that QE boosts bond prices. This suggests the possibility of a behavioural channel for the observed effects of actual QE operations on bond yields.
Keywords: C90; D84; 330; Quantitative easing; experimental asset market; expectation dynamics